The Revived World in the Movie Avatar by James Cameron — the Subjective Nature of Fauna and Flora - Weber, Eryk (The Motifs of Fauna and Flora in Literature and Culture, 2018)
The work raises the problem of the subject in the non-human world. Based on the movie Avatar (dir. James Cameron, 2009) shows the potentional of understanding the subject in the world of plants and animals. The movie was used in the work as far-reaching metaphor of the world in which we live, or to maximize the specific attitudes and theories that we use in the our environment and science. This analysis was confronted with today’s level of subject understanding in our world and invites the readers to reflect on the status of other living creatures.